A systematic review of the effect of foot orthoses and shoe characteristics on balance in healthy older subjects. (April 2016) - Aboutorabi, Atefeh; Bahramizadeh, Mahmood; Arazpour, Mokhtar; Fadayevatan, Reza; Farahmand, Farzam; Curran, Sarah; Hutchins, Stephen W
Background: Foot orthoses are used to optimize lower extremity function and can improve postural stability by enhancing the afferent somatosensory feedback available to the central nervous system. Objective: The aim of this review was to evaluate the effect of foot orthoses on balance control in older subjects. Study design: Systematic review. Methods: The search strategy was based on the Population Intervention Comparison Outcome method. A search was performed in PubMed, Science Direct, Google Scholar, and ISI Web of Knowledge databases by using selected keywords. A total of 22 articles were selected for final evaluation. Results: The results demonstrated that older people should be advised to wear thin, hard-soled footwear with high collars to reduce the risk of falling. The findings for insoles demonstrated an increase in balance control via vibratory or magnetic insoles, but textured insoles do not appear to be beneficial for balance improvement. Conclusion: Foot orthoses improve postural stability via a somatosensory or biomechanical effect. Use of footwear with the proper features can be an appropriate intervention in order to increase the balance in the older population and reduce falls. Clinical relevance: Loss of balance is an important factor in increasing the risk of falling in older subjects. Foot orthoses can improve functional measures of stability in older adults. In this review, results from studies suggest a number of recommendations regarding the optimal footwear for older people to reduce the risk of falling.